2019
DOI: 10.1136/archdischild-2018-316394
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of children with tuberous sclerosis complex

Abstract: AimEvaluation of impaired quality of life (QOL) of Malaysian children with tuberous sclerosis complex (TSC) and its possible risk factors.MethodCross-sectional study on 68 parents of Malaysian children aged 2–18 years with TSC. QOL was assessed using proxy-report Paediatric Quality of Life Inventory (PedsQL) V.4.0, and scores compared with those from a previous cohort of healthy children. Parents also completed questionnaires on child behaviour (child behaviour checklist (CBCL)) and parenting stress (parenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
2
11
1
1
Order By: Relevance
“…Our findings indicate that neuropsychiatric disorders seriously affect patients' QOL and require careful attention from neurologists. However, our results are quite different from those of previous studies: There were no significant differences in any of the QOL domains by age 20 . It was first found that the TSC1/TSC2 group reported significantly worse QOL.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings indicate that neuropsychiatric disorders seriously affect patients' QOL and require careful attention from neurologists. However, our results are quite different from those of previous studies: There were no significant differences in any of the QOL domains by age 20 . It was first found that the TSC1/TSC2 group reported significantly worse QOL.…”
Section: Discussioncontrasting
confidence: 99%
“…Notably, the psychosocial health scores were significantly lower than the physical health scores, which was consistent with previous studies 20,21 . As in previous studies, TANDs can exist at all ages 5 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There are two recent studies conducted in Asia assessing the QoL of TSC patients in Malaysia and mainland China respectively (29,30). We compared these two studies with our study and identi ed 3 distinctive differences.…”
Section: Comparison With Other Studies On Qol Of Tsc Populationmentioning
confidence: 98%
“…Data regarding HRQoL in Asian TSC population is limited. Two cross-sectional studies evaluated the QoL of TSC patients using PedsQL in China and Malaysia respectively, but their study populations were limited to the pediatric age group (29,30). Another retrospective analysis study documented the QoL of postepileptic surgery TSC patients in China (31).…”
Section: Introductionmentioning
confidence: 99%